Homonym Vocabulary in Arabic - Suhada, Oman Karya; Pritantoro, Wendy Morrizha; Huda, Miftachul (Institut Agama Islam Negeri Kerinci, 2022)
Sometimes the expression of a word has two meanings because it is called in different places, in linguistic studies it is called a homonym and in balaghah science, it is called Jinas. The purpose of this study is to find out homonym vocabulary in Arabic, especially in the form of isim jamid. This study uses a descriptive method with a content analysis model. The data source is several Arabic vocabulary from the dictionary